2013
DOI: 10.1038/bonekey.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 signaling and other recruitment and homing pathways in fracture repair

Abstract: Cell recruitment, migration and homing to the fracture site are essential for the inflammatory process, neovascularization, chondrogenesis, osteogenesis and ultimately bone remodeling. Mesenchymal stem cells (MSCs) are required to navigate from local sources such as the periosteum and local bone marrow, and may also be recruited from the circulation and distant bone marrow. While the local recruitment process may involve matrix binding and degradation, systemic recruitment may utilize extravasation, a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 132 publications
4
100
0
Order By: Relevance
“…Endothelial cells, osteoblasts and reticular cells produce CXCL12 in these organs (25). We observed that the CXCR4 blockade with plerixafor (12) prevented the homing of cells to the BM and the effect lasted longer when G-CSF was co-administered (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells, osteoblasts and reticular cells produce CXCL12 in these organs (25). We observed that the CXCR4 blockade with plerixafor (12) prevented the homing of cells to the BM and the effect lasted longer when G-CSF was co-administered (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for the action of CXCL12 on the skeletal system in inducing chondrocyte hypertrophy and BMP-dependent osteoblastic differentiation of progenitors, (23,33,34) as well as cell recruitment in bone injuries. (38,39) An appropriate control of CXCL12 expression appears critical, in fact, long-term continuous treatment before fracture or load-induced bone formation can inhibit bone production. (40,41) We identified the temporally regulated expression pattern of CXCL12 and showed that it is initially induced by the fracture event and then decreases with the progression of the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoxia by the expression of the hypoxia-inducible factor 1-α (HIF-1α) subunit transcription factor may induce the upregulation of SDF1 and ultimately regulate the homing of progenitor cells. The SDF1/CXCR4 (CXC chemokine receptor R4) axis is thought to be a master mediator of MSC recruitment and migration [Yellowley, 2013]. Because of the hypoxic condition at the injured (fracture) site, it is possible that the expression of chemokines such as SDF1 is regulated by hypoxia and HIF-1α.…”
Section: Msc Homing and Recruitment To Bone Defectsmentioning
confidence: 99%